FIRST CITATION OF THE EXOTIC PARASITE Lernaea cyprinacea L., 1758 (CRUSTACEA, COPEPODA, LERNAEIDAE) AFFECTING Cnesterodon decemmaculatus JENYNS, 1842 (OSTEICHTYES, CIPRINODONTIFORMES, POECILIDAE) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
Lernaea cyprinacea is an extremely invasive exotic parasitic copepod that was introduced into the Neotropical region in the 1980s. It affects both farmed and wild native fish. In Uruguay it has been recorded in eight non-native species of ornamental fish and in five native species. In spring 2018 fish were sampled in a dugout pond in the Montevideo Department, where 20 specimens of Cnesterodon decemmaculatus were captured, some of which visibly parasitized by the copepod. This is the first report of this parasite affecting C. decemmaculatus. The prevalence of the parasitosis was 75% (15/20), while the average intensity of infestation was 2.73 parasites per fish(41/15). There is a positive correlation between the intensity of the parasitosis and the size of the fish. The preferred area for fixation of parasites is the ventral part of the body, followed by the caudal peduncle.